Discrete investment and tax competition when firms shift profits - Sven Stöwhase (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2006)
In this paper, we model the tax setting game between two revenue maximizing countries which compete for the location of a single production plant owned by a multinational firm. We introduce the possibility that the multinational can shift a fraction of its profits out of the country where the production plant is located. In this framework, it is investigated how a change in the costs of profit shifting affects equilibrium tax rates. We show that in most cases, equilibrium tax rates of the two countries will be higher under profit shifting than without. Unless profit shifting does not become too easy, the strategic adjustment of profit tax rates will typically harm the multinational firm.
Keywords: F23; H25; H32; 330; tax competition; profit shifting; multinational enterprises; discrete investment